2018
DOI: 10.1038/s41392-018-0026-5
|View full text |Cite
|
Sign up to set email alerts
|

RNA-binding protein LIN28B inhibits apoptosis through regulation of the AKT2/FOXO3A/BIM axis in ovarian cancer cells

Abstract: LIN28B is an evolutionarily conserved RNA-binding protein that regulates mRNA translation and miRNA let-7 maturation in embryonic stem cells and developing tissues. Increasing evidence demonstrates that LIN28B is activated in cancer and serves as a critical oncogene. However, the underlying molecular mechanisms of LIN28B function in tumorigenesis are still largely unknown. Here we report that LIN28B was expressed in over half of the patients with epithelial ovarian cancer who were examined (n = 584). Functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 50 publications
(71 reference statements)
1
55
0
Order By: Relevance
“…In fact, in response to mitochondrial damage, the cell recruited the lysosome to degrade the damaged mitochondria. However, this protective mitophagy was significantly inhibited by ox‐LDL (Dasa et al, ; Lin et al, ). Therefore, our findings provide further insight into the mechanism of mitochondrial injury induced by the inflammatory response (Cui et al, ; Goiran et al, ), which also provide a potential target to increase mitochondrial resistance against inflammatory damage.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, in response to mitochondrial damage, the cell recruited the lysosome to degrade the damaged mitochondria. However, this protective mitophagy was significantly inhibited by ox‐LDL (Dasa et al, ; Lin et al, ). Therefore, our findings provide further insight into the mechanism of mitochondrial injury induced by the inflammatory response (Cui et al, ; Goiran et al, ), which also provide a potential target to increase mitochondrial resistance against inflammatory damage.…”
Section: Discussionmentioning
confidence: 99%
“…Rs2153127, as one of instrumental variables of AAM in our MR study, is indicated to be associated with the expression of LIN28B in pituitary (https://www.gtexportal.org/home/snp/rs2153127). LIN28B was reported to be related to the proliferation, migration, and apoptosis of ovarian cancer . Further studies on variants associated with AAM or in the HPG axis may be beneficial to identify additional genetic variants for ovarian cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…LIN28B was reported to be related to the proliferation, migration, and apoptosis of ovarian cancer. 74,75 Further studies on variants associated with AAM or in the HPG axis may be beneficial to identify additional genetic variants for ovarian cancer risk. Additionally, the negative association between AAM and EOC risk could be explained by hormone-related "incessant ovulation" hypothesis, which supported increasing numbers of lifetime ovulations with higher risk of ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…LIN28B, with its paralog LIN28A, plays pivotal roles in regulating multiple processes that shape normal development, including the cell cycle and apoptosis, self-renewal, glycolysis, and oxidative phosphorylation, among others. (5) (6) These same processes are often subverted in a variety of tumors; accordingly, LIN28B is deregulated in multiple tumor histotypes, including cancers of the colon (7) and ovary (8), Wilms tumor (9), germ cell tumors (10), and hepatocellular carcinomas. (11) Targeted LIN28B overexpression in respective murine tissues leads to the development of neuroblastoma (3), colon cancer (11) (12), and liver cancer (11), credentialing LIN28B as a bona fide oncogene.…”
Section: Introductionmentioning
confidence: 99%